2006
DOI: 10.1063/1.2364601
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and band offsets of ultrathin HfO2–Y2O3 composite films studied by photoemission and x-ray absorption spectroscopies

Abstract: The authors have investigated ultrathin HfO2–Y2O3 composite films by photoemission spectroscopy and x-ray absorption spectroscopy (XAS) to elucidate the Y2O3 composition dependence of crystallization and band offsets. The authors have found that the crystal structure of ultrathin films can be predicted by the detailed spectral structure between 540 and 550eV in XAS. Photoemission spectroscopy and XAS reveal that the films of x=0 and 0.05 are mainly in a monoclinic phase, while those of x=0.10 and 0.20 are in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
3
9
1
Order By: Relevance
“…The increase with Gd doping in the intensity of the photoemission features in the oxygen 2 p region of the valence band, at 5 to 10 eV binding energy, relative to the Hf 4 f features at 18-21 eV binding energies, suggests that there are Gd 5d contributions to the these lower binding energy features, as is expected from studies of HfO 2 -Y 2 O 3 composite films [27]. In Figure 2, one can clearly see a shoulder on the broad photoe mission peak at the binding energy of 9-10 eV.…”
supporting
confidence: 55%
“…The increase with Gd doping in the intensity of the photoemission features in the oxygen 2 p region of the valence band, at 5 to 10 eV binding energy, relative to the Hf 4 f features at 18-21 eV binding energies, suggests that there are Gd 5d contributions to the these lower binding energy features, as is expected from studies of HfO 2 -Y 2 O 3 composite films [27]. In Figure 2, one can clearly see a shoulder on the broad photoe mission peak at the binding energy of 9-10 eV.…”
supporting
confidence: 55%
“…[9][10][11][12][13][14][15][16][17] However, considering the occurrence of ferroelectricity in Y:HfO 2 thin films, a simple monoclinic=cubic phase mixture or intermediate tetragonal phases seem contradictory, since neither the cubic=tetragonal nor the monoclinic phases in HfO 2 possess ferroelectric space groups. 29 A close examination of the GI-XRD diffractograms presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the cubic phase. Y:HfO 2 thin films have a large bandgap, 11 are temperature stable, 21 CMOS compatible, 23,24 and due to the availability of mature atomic layer deposition (ALD) processes, 13 they are capable of conformal 3D integration. Therefore Y:HfO 2 is considered a promising material for future, highly scaled ferroelectric memories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It has been demonstrated that Y 2 O 3 doping stabilizes HfO 2 in the cubic phase. [5][6][7][8] Doping of HfO 2 by Er, [7][8][9] Gd, 8,10,11 and many other rare earth elements 8 also induces a monoclinic to cubic phase transition. The gadolinium doping of a number of wide band gap semiconductors [12][13][14] suggested that Gd doping of HfO 2 may lead to a dilute magnetic semiconductor.…”
mentioning
confidence: 99%